Morphological Identification and Phylogenetic Analysis of Laelapin Mite Species (Acari: Mesostigmata: Laelapidae) from China - Yang, Huijuan; Yang, Zhihua; Dong, Wenge (Korean journal of parasitology, 2022)
Laelapinae mites are involved in transmission of microbial diseases between wildlife and humans, with an impact on public health. In this study, 5 mite members in the subfamily Laelapinae (laelapin mites; LM) were morphologically identified by light microscopy, and the phylogenetic relationship of LM was analyzed in combination with the sequence information of part of the LM cytochrome oxidase subunit I (cox1) gene. The morphological identification revealed that 5 mites belonged to the genera Laelaps and Haemolaelaps, respectively. Sequence analysis showed that the ratio of non-synonymous mutation rate to synonymous mutation rate of LM was less than 1, indicating that the LM cox1 gene had undergone purifying selection. Phylogenetic analysis showed that the Laelapinae is a monophyletic group. The genera Haemolaelaps and Hyperlaelaps did not separated into distinct clades but clustered together with species of the genus Laelaps. Our morphological and molecular analyses to describe the phylogenetic relationships among different genera and species of Laelapinae provide a reference for the improvement and revision of the LM taxonomy system.